Pengaruh Respon dan Keikutsertaan Wajib Pajak dalam Program Tax Amnesty terhadap Kepatuhan Wajib Pajak di Bekasi - Tutty Nuryati; Muhammad Hasbi (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2017)
This study aims to determine the effect of taxpayer response and participation in the tax amnesty program on Taxpayer compliance, both formal compliance and material compliance. The hypothesis is the response and taxpayer participation in the tax amnesty program affect the formal compliance and taxpayer material. This research is located in Bekasi with taxpayer analysis unit registered in KPP Pratama Bekasi Utara, Bekasi Selatan, CikarangUtara, Cikarang Selatan, and Cibitung. Data collection techniques were conducted with questionnaires and interviews and literature study. Data analysis using Structural Equation Modelling (SEM). The result of the research found: 1) there is a positive correlation between Taxpayer response to tax amnesty program to Taxpayer participation in Tax amnesty program 2) there is a positive relationship between Taxpayer response to tax amnesty program to formal Compliance 3) there is no positive relationship between the obligatory participation Tax on the tax amnesty program on formal compliance 4) there is a positive relationship between taxpayers' response to the tax amnesty program on material compliance 5) there is no positive correlation between formal compliance of Taxpayer to material compliance 6) there is no positive relationship between taxpayer participation to compliance material.